2012
DOI: 10.1063/1.4749270
|View full text |Cite
|
Sign up to set email alerts
|

In-plane dielectric properties of epitaxial Ba0.7Sr0.3TiO3 thin films grown on GaAs for tunable device application

Abstract: Evolution of local work function in epitaxial VO2 thin films spanning the metal-insulator transition Appl. Phys. Lett. 101, 191605 (2012) Anisotropic electrical properties in bismuth layer structured dielectrics with natural super lattice structure Appl. Phys. Lett. 101, 012907 (2012) We have epitaxially deposited ferroelectric Ba 0.7 Sr 0.3 TiO 3 (BST) thin films grown on GaAs substrate via SrTiO 3 buffer layer by laser molecular beam epitaxy. Structural characteristics of the heterostructure were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Since the successful synthesis of high temperature superconducting yttrium barium copper oxide (YBa 2 Cu 3 O 7 ) films in an efficient and epitaxial way, 33 PLD has become one of the most widely used techniques for the deposition of complex oxide thin films, [34][35][36][37] heterostructures, [38][39][40][41][42][43] and well controlled interfaces. 44 As shown in Fig.…”
Section: Overview Of Pld For 2d Filmsmentioning
confidence: 99%
“…Since the successful synthesis of high temperature superconducting yttrium barium copper oxide (YBa 2 Cu 3 O 7 ) films in an efficient and epitaxial way, 33 PLD has become one of the most widely used techniques for the deposition of complex oxide thin films, [34][35][36][37] heterostructures, [38][39][40][41][42][43] and well controlled interfaces. 44 As shown in Fig.…”
Section: Overview Of Pld For 2d Filmsmentioning
confidence: 99%
“…BaTiO 3 has been deposited on SrTiO 3 -buffered GaAs substrates by MBE [106, 128] or by laser MBE [129, 130]. Huang et al reported the growth by laser MBE of c -axis oriented films [129].…”
Section: Mbe Of Batio3 On Semiconductors: Growth and Crystalline Strumentioning
confidence: 99%
“…Previously, several types of heterostructures of perovskite oxide thin lms and GaAs have been studied by our group. [87][88][89][90][91][92][93] Very recently, we combined CVD-grown graphene sheets with GaAs wafers. Single-and bi-layer graphene sheets were transferred onto an ntype GaAs substrate with about 200 nm SiO 2 as an insulating layer to form a graphene/GaAs Schottky barrier, as schematically shown in Fig.…”
Section: Solar Cellsmentioning
confidence: 99%